2005
DOI: 10.1007/s00421-005-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pulmonary $$\dot{V} \hbox{O}_{2}$$ and femoral artery blood flow and their relationship during repeated bouts of heavy exercise

Abstract: The mechanism that alters the pulmonary VO2 response to heavy-intensity exercise following prior heavy exercise has been frequently ascribed to an improvement in pre-exercise blood flow (BF) or O(2) delivery. Interventions to improve O(2) delivery have rarely resulted in a similar enhancement of VO2. However, the actual limb blood flow and VO2 dynamics in the second bout of repeated exercise remain equivocal. Seven healthy female subjects (21-32 years) performed consecutive 6-min (separated by 6 min of 10 W ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 68 publications
2
43
0
Order By: Relevance
“…These findings are consistent with previous studies examining prior exercise in both young and older adults and suggest a greater muscle perfusion prior to and throughout Mod 2 (12,22,24). A greater muscle oxygenation is consistent with previous demonstrations of elevated HR in older adults (12,51) and greater limb conduit artery blood flow in young adults (16,17,41) during baseline exercise following heavy-intensity exercise and very early in the transition to a subsequent bout of exercise. There is evidence that O 2 availability is impaired during the transition to exercise in muscle from older animals and human subjects (3,11,12,14,39,43,44,49), and thus prior exercise in older adults likely improves O 2 availability in Mod 2 compared with Mod 1 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with previous studies examining prior exercise in both young and older adults and suggest a greater muscle perfusion prior to and throughout Mod 2 (12,22,24). A greater muscle oxygenation is consistent with previous demonstrations of elevated HR in older adults (12,51) and greater limb conduit artery blood flow in young adults (16,17,41) during baseline exercise following heavy-intensity exercise and very early in the transition to a subsequent bout of exercise. There is evidence that O 2 availability is impaired during the transition to exercise in muscle from older animals and human subjects (3,11,12,14,39,43,44,49), and thus prior exercise in older adults likely improves O 2 availability in Mod 2 compared with Mod 1 .…”
Section: Discussionsupporting
confidence: 91%
“…4 in Gurd et al 2006). After HVY exercise, heart rate (DeLorey et al 2004;Gurd et al 2005;Scheuermann et al 2002) and NIRS-derived measures of oxy-and total hemoglobin/myoglobin [reflecting greater local (microvascular) perfusion] (DeLorey et al 2007;DeLorey et al 2004;Gurd et al 2005Gurd et al , 2006 remained elevated prior to and throughout the subsequent bout of exercise, while conduit artery muscle (i.e., bulk) blood flow remained elevated at baseline and during the immediate onset of exercise (DeLorey et al 2007;Endo et al 2005;Fukuba et al 2004;Hughson et al 2003;Jones et al 2006;MacDonald et al 2001;Paterson et al 2005). Based on these findings, it was argued that the speeding of _ VO 2p kinetics seen after HVY in these individuals is due, in part, to the removal of the constraint imposed by an inadequate local microvascular blood flow distribution and O 2 delivery during the exercise on-transition.…”
Section: Introductionmentioning
confidence: 92%
“…However, as demonstrated recently, the reduction in s _ VO 2p after prior HVY priming exercise was related directly to how ''slow'' the _ VO 2p response was to the ''unprimed'' state (Gurd et al 2005(Gurd et al , 2006, and thus failure to observe a measurable reduction in s _ VO 2p in these studies was not unexpected. A prior bout of HVY was shown previously to increase heart rate (DeLorey et al 2004;Gurd et al 2005;Scheuermann et al 2002) and cardiac output (Faisal et al 2009); to increase muscle perfusion, as shown by elevated bulk muscle blood flow (determined using Doppler ultrasonography) (DeLorey et al 2007;Endo et al 2005;Fukuba et al 2004;Hughson et al 2003;MacDonald et al 2001;Paterson et al 2005) and elevated local muscle oxyand total hemoglobin concentrations (measured using NIRS) (DeLorey et al 2004(DeLorey et al , 2007Gurd et al 2006;Gurd et al 2005;Jones et al 2006); and to increase mitochondrial PDH activity (Gurd et al 2006). In the present study, the speeding of _ VO 2p kinetics in MOD2 in HYPO (and CON), without a change in deoxygenation kinetics, along with a greater D[Hb TOT ] and D[O 2 Hb], suggest that greater muscle perfusion and distribution prior to and during MOD2 resulted in a higher muscle blood flow-to-O 2 utilization ratio during the exercise transition which would maintain a higher microvascular PO 2 and greater diffusive delivery of O 2 into the muscle.…”
Section: D[hhb]mentioning
confidence: 97%
“…Furthermore, during heavy-intensity exercise performed in a supine or prone position, where muscle perfusion pressure is reduced, studies have consistently suggested that O 2 availability is a limiting factor of muscle O 2 consumption at the onset of exercise (Endo et al 2005;Fukuba et al 2004;Hughson et al 1993;Jones et al 2006;Perrey et al 2001). For example, Jones et al (2006) used the relative total haemoglobin/myoglobin concentration (D[Hb tot ]) measured using near-infrared spectroscopy to indicate that O 2 delivery was enhanced at the onset of a repeated bout of supine cycling, and an increased O 2 availability in the muscle was attributed to the reduction in the time constant (tau, s) of the fundamental, phase II VO 2 kinetic response (s 38 vs. 24 s).…”
Section: Introductionmentioning
confidence: 99%